The utility of intact parathyroid hormone level in managing hypocalcemia after thyroidectomy in children. (October 2019) - Jiang, Wen; Lee, Euyhyun; Newfield, Ron S.
Abstract: Introduction: Hypocalcemia is a common complication after thyroidectomy. Intact parathyroid hormone (PTH) has been successfully used as a predictive indicator for hypocalcemia in adults during the postoperative period. We aim to demonstrate the utility of PTH in predicting and managing postoperative hypocalcemia following thyroidectomy in pediatrics. Methods: The study is a retrospective case series including 38 patients up to 18 years of age who underwent total or completion thyroidectomy from 1/1/2010 to 12/31/2016 at a tertiary pediatric academic center. Patient demographics, pathology, postoperative PTH, serum calcium, and length of stay were analyzed. Results: The median age was 14.3 years (range of 4.3–18.4 years) with 84.2% being female. Thyroid malignancy was noted in 25 patients, and 13 had benign pathology including 8 patients with multinodular goiter and 5 with Grave's disease. In this serie, 63.2% (24/38) developed hypocalcemia (serum calcium <8.5 mg/dL) postoperatively. The median PTH of 15.8 pg/mL in the hypocalcemic group was significantly lower than the median PTH of 41.6 pg/mL in the normocalcemic group (p < 0.001). Using a PTH threshold of 26 pg/mL, hypocalcemia was predicted with a sensitivity of 75%, and specificity of 100%. Six patients with calcium <7.5 mg/dL received teriparatide injections to avoid intravenous calcium replacement. The length of hospital stay for normocalcemic patients was 1.7 ± 0.8 days vs. 2.9 ± 1.4 days for hypocalcemic patients (p = 0.002). We found no correlation between the incidence of hypocalcemia and pathologic indication for surgery. Completion thyroidectomy was associated with a lower risk of hypocalcemia when compared to total thyroidectomy (p = 0.01) and neck dissections carried an increased risk of postoperative hypocalcemia (p = 0.04). Conclusion: Postoperative PTH level has an excellent specificity in predicting hypocalcemia in this pediatric cohort using a threshold of PTH ≤ 26 pg/mL. Those with PTH >26 pg/mL may avoid hypocalcemia by oral calcium replacement with outpatient follow-up. We did not identify a reliable PTH cutoff value above which pediatric patients may be safely discharged immediately following surgery. Adult guideline or pathways that advocate for outpatient thyroidectomy surgery based on normal PTH ≥10 pg/mL in the recovery room may not apply to children.